2014
DOI: 10.2514/1.61114
|View full text |Cite
|
Sign up to set email alerts
|

Wake Sensing for Aircraft Formation Flight

Abstract: It is well established that flying aircraft in formation can lead to improved aerodynamic efficiency. However, successfully doing so is predicated on having knowledge of the lead aircraft's wake position. Here, a wake-sensing strategy for estimating the wake position and strength in a two-aircraft formation is explored in a simplified proof-ofconcept setting. The wake estimator synthesizes wing-distributed pressure measurements, taken on the trailing aircraft, by making use of an augmented lifting-line model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The results showed that vortex location and strength are observable using two velocity sensors, and that active motion of the airfoil (i.e., flapping) improves vortex observability, similar to the way that the dither signal in [13] improved estimator performance. An unscented Kalman filter (UKF) was used in simulation to estimate the location and strength of vortices in the wake of the flapping airfoil [14].…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…The results showed that vortex location and strength are observable using two velocity sensors, and that active motion of the airfoil (i.e., flapping) improves vortex observability, similar to the way that the dither signal in [13] improved estimator performance. An unscented Kalman filter (UKF) was used in simulation to estimate the location and strength of vortices in the wake of the flapping airfoil [14].…”
mentioning
confidence: 68%
“…The activation of each sensor is given by α α∕ν, and the resulting condition number of the observability Gramian is γ. If the solution of problem (14) yields sensor activations such that α i ∈ f0; 1g ∀ i (within numerical precision), then the solution to the relaxed problem (14) is also the solution to problem (13). Otherwise, the original problem (13) must be solved using mixed-integer programming techniques.…”
Section: Observability-based Optimal Sensor Placementmentioning
confidence: 98%
See 3 more Smart Citations